51.1k views
4 votes
Let
p=x^(2)+6

Which equation is equivalent to
(x^(2)+6)^(2)-21=4x^(2)+24 in terms of
p?

User Tehhowch
by
5.6k points

1 Answer

3 votes

Answer:

Hello There. ☆~---~--___●♡●__~--☆ Since p = x² - 7, you can substitute/plug in p for x² - 7

So:

(x² - 7)² - 4x² + 28 = 5

(p)² - 4x² + 28 = 5 You can factor out -4 from (-4x² + 28)

p² - 4(x² - 7) = 5 Plug in p

p² - 4p = 5 Subtract 5

p² - 4p - 5 = 0 And, your correct answer is C.

Hope It Helps!~

ItsNobody~ ☆

User Mr Punch
by
5.4k points